Implementasi Prinsip Hukum Humaniter Internasional dan Etika Militer dalam Konflik Rusia-Ukraina (2014-2025): Pendekatan Normatif-Yuridis dan Historis-Kritis - Nur Wahyudi; Nurulloh Zemy Prasetyo; Tarsisius Susilo; Benny Limbong; Agus Soeprianto (Jurnal Hukum Lex Generalis, 2025)
This research analyzes the application of International Humanitarian Law principles (distinction, proportionality, humanity, military necessity) in the Russia–Ukraine conflict (2014–2025), identifies serious violations (bombing of civilian facilities, prohibited weapons, forced deportation), and explores contemporary military ethical reflections related to the use of autonomous drones, cyber operations, and the Internet of Battlefield Things. The results show distortions in the implementation of IHL in operational "grey zones," the low effectiveness of international law enforcement, and the emergence of new moral dilemmas in war technology. In conclusion, adaptive enforcement mechanisms and adequate ethical frameworks are needed to safeguard civilian protection in modern conflicts.